Magombok reimagining traditional performance (Ritual-Theatre) for heritage sustainability - Sharifuddin Zainal; Mohd. Kipli Abd. Rahman; Amsalib Pisali; Mashor Awang Long; Muhammed Syafiq Salleh; Khairul Kamsani (AMER ABRA cE-Baby e-International Publishing House, Ltd, 2025)
Facing cultural erosion, the endangered Magombok ritual of Sabah's Bajau Laut may be revitalized through theatrical transformation. This research explores bridging ritual and performance, guided by Schechner and Turner's theories. By integrating performance elements with ritual perspectives, the study aims to empower local identity, preserve cultural heritage, and enrich Sabah's traditional theatre scene. Practical adaptation methods offer a path to cultural sustainability. The reimagined Magombok holds potential as a cultural tourism asset, boosting the socio-economic well-being of the local community and ensuring the tradition's continued existence. This innovative approach offers a sustainable future for cultural preservation.